Dampak Modernisasi terhadap Kearifan Lokal di Kalangan Masyarakat Baduy Luar di Kabupaten Lebak, Banten, Indonesia - Alya Raissa Putri; Athaya Raisa Aqilah; Nabilah Fikri Hardiani; Candrika Adhiyasa; Syifa Salsabila (Jurnal Penelitian Pendidikan IPA, 2026)
The Baduy are one of the indigenous communities in Indonesia who continue to preserve local wisdom rooted in Sundanese customary law and reside in Lebak Regency, Banten Province. Among the Baduy community, the Baduy Luar demonstrate a relatively adaptive interaction with modernization while maintaining adherence to customary values. This study aims to analyze the forms of local wisdom among the Baduy Luar community, examine the roles of the community and local government in preserving these values, and identify the impacts of modernization on their sustainability. The novelty of this research lies in the use of an ethnoecological perspective to explore the relationship between local wisdom, environmental practices, and socio-cultural adaptation within the context of modernization. This study employed a qualitative approach with an ethnoecological perspective. Data were collected through in-depth interviews with six purposively selected informants consisting of customary leaders, village officials, and representatives of both older and younger generations of the Baduy Luar community, supported by direct observations and documentation. The research was conducted in Kanekes Village, Leuwidamar District, Lebak Regency, on August 10–11, 2024. Data were analyzed using thematic analysis through stages of data reduction, categorization, interpretation, and triangulation of sources and methods to ensure data validity. The findings indicate that local wisdom within the Baduy Luar community is reflected in seven cultural elements: language, knowledge systems, social organization, subsistence and technological systems, livelihood patterns, religious beliefs, and traditional arts. The preservation of these values is primarily maintained through adherence to customary law, while local government involvement is manifested through regional regulations that recognize and protect indigenous traditions. However, modernization has also increased dependence on modern elements, resulting in economic reliance, cultural penetration, social transformation, and the emergence of local resistance as a form of cultural resilience.